Department of Biotechnology, Periyar University, Salem – 636011, Tamil Nadu, India. - ZURAIDA A.R,; FATIN LIYANA IZZATI K.,; AYU NAZREENA O., (International Journal of Pharma and Bio Sciences, 2014)
In vitro micropropagation of Melicope lunu-ankenda was carried out by shoot regeneration from explants followed by rooting of the multiplied shoots. Two types of culture media, MS and WPM media, supplemented with the cytokinin 6- benzylaminopurine (BAP) (0, 0.5, 1.0, 3.0 and 5 mg/l) were used for shoot initiation. For shoot propagation, BAP was tested in combination with kinetin (KIN). Explants from lateral shoots responded better to shoot initiation as compared with those derived from shoot apices, when cultured on MS medium supplemented with 1 mg/L BAP. The combination of BAP (3.0 mg/l) and KIN (1 mg/L) was superior to all other hormonal treatments for shoot proliferation with a maximum of 25 shoots per explants being obtained. The auxins indole-3-butyric acid (IBA) and indole-3-acetic acid (IAA) were used in six concentrations (0.1, 0.2, 0.5, 1.0 and 2.0 mg/l) for root induction from the regenerated shoots. MS supplemented with IBA (0.5 mg/l) was the best medium to induce rooting from regenerated shoots. A plantlet survival rate of greater than 85% was achieved during acclimatization. The availability of this protocol is a key step towards large scale production of Melicope lunu-ankenda for the exploitation of its pharmaceutical potential in Malaysia.